Analysis of Public Awareness of Navigational Aids in Navigational Waters Southeast Sulawesi (Case Study of Navigation District Office Type A Class III Kendari) - Safrianto, Muhammad; Adam, Pasrun; Tambunan, Rince; Nur, Muh.; Rahmah, Wahyuni (Jurnal Global Ilmiah, 2025)
The aim to be achieved in this research is to determine and analyze public awareness of shipping navigation aids in Southeast Sulawesi waters at the Kendari Type A Class III Navigation office. The research method used is a descriptive qualitative approach. Data collection tools include observation, interviews and documentation. The informants in this research were the Head of Installation, the Shipping Navigation Aids technician, with the Head of the Shipping Navigation Aids Section as the key informant. The results of this research show that: Public awareness of shipping navigation aids at the Kendari Type A Class III Navigation District Office. Researchers can conclude that the Kendari Class III Type A Navigation District office has not been optimal in conducting socialization regarding shipping navigation aids to the community along the coast. and around the location of the facility. As a result, most people do not know the role and function of shipping navigation aids in supporting shipping safety in Southeast Sulawesi waters. However, through interviews conducted, the community stated that if they understood the function and use of shipping navigation aids, they would be better prepared to maintain and protect these facilities from the actions of irresponsible groups.